MEASURES AND STAGES OF DEVELOPING AN INVESTMENT STRATEGY FORCOMMERCIAL BANKS UNDER MARTIAL ARTS CONDITIONS - HAVRYLOVA, Nataliia; PEREVERZIEV, Yevhen (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The investment strategy of a commercial bank serves as a strategic guideline for the entire investment management system, determining priority areas for resource investment, criteria for the effectiveness of investment projects, as well as mechanisms for controlling and regulating the investment portfolio in conditions of market uncertainty. The investment strategy of a commercial bank not only serves as a capital management mechanism, but also forms an important tool for the bank’s strategic positioning in a competitive environment. Its effectiveness largely depends on the bank’s ability to flexibly adapt to market changes, assess risks, and at the same time realize the potential for growth through effective management of investment activities. A feature of the investment strategy is its dynamic nature, which requires constant monitoring of the external investment environment, assessment of macroeconomic trends, and adaptation to changes in the structure of demand for investment resources. Given the cyclical nature of economic development and the constant updating of financial instruments, the investment strategy must be flexible enough to respond in a timely manner to changes in the investment market situation. The paper considers the stages of developing the investment strategy of commercial banks, their types and directions depending on the overall development strategy of the bank, considers examples of implementing the investment strategy, and analyzes the types of investment strategy of commercial banks depending on the economic situation. Significant attention is paid to the analysis of the investment portfolio of commercial banks of Ukraine, the priorities of the investment strategy of commercial banks, and key changes in the target guidelines of the investment strategy of commercial units of Ukraine for the period 2022-2024 are outlined.